Covalent attachment of an electroactive sulfydryl reagent in the active site of cytochrome P450(cam) as revealed by the crystal structure of the modified protein - Di Gleria, K; Nickerson, D; Hill, H; Wong, L; Fulop, V (1998)
A novel electroactive sulfydryl-specific reagent, N-(2-ferrocenylethyl)maleimide (Fc-Mi), was used to attach a redox-active reporter group to cytochrome P450(cam) from Pseudomonas putida. The crystal structure of the modified enzyme was determined at 2.2 Å resolution (R(cryst) = 0.18) and compared to the structure of the wild-type enzyme complexed with its natural substrate. The results showed that two molecules of the electroactive modifier were attached to the protein. One of the ferrocenes was linked to Cys85 via the maleimide moiety and occupied the camphor-binding site in the substrate pocket. The other ferrocene was linked to Cys136 on the surface of the protein. :Significant conformational changes were observed on the distal side of the heme when camphor was replaced by ferrocene. The shift in the Soret band from 392 to 417 nm upon modification arose from the binding of a water molecule to the heme iron immediately below the ferrocene in the active site of the modified enzyme. The electrochemistry of the labeled enzyme showed clear signals originating both from the heme and from the covalently linked ferrocenes. The direct current cyclic voltammogram revealed a striking positive shift in the heme redox potential of the ferrocene-containing P450(cam) from -380 mV for the camphor-bound wild-type protein to -280 mV for the modified protein.